Pemeliharaan Bahasa di Ruang Publik: Analisis Semiotik terhadap Lanskap Linguistik Kota Sukabumi - Juanda, Mochammad Rizki; Kurniawan, Eri (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research aims to uncover the language usage that emerges in the area of Sukabumi City. A total of 165 data were collected through smartphone cameras. The collected data were then analyzed using a semiotic approach and interpreted by considering all aspects that appear in each sign. The findings discoverd that public signage uses Indonesian language, while some also incorporate Sundanese language in their writings. On the other hand, private signage exhibits varied results, utilizing Indonesian, English, Sundanese, or a combination of two or three of these languages. Based on the findings, it can be observed that the use of language, both in public and private signage, is not done haphazardly.